Reversible Electronic Solid–Gel Switching of a Conjugated Polymer. Issue 2 (28th October 2019) - Gladisch, Johannes; Stavrinidou, Eleni; Ghosh, Sarbani; Giovannitti, Alexander; Moser, Maximilian; Zozoulenko, Igor; McCulloch, Iain; Berggren, Magnus
Abstract: Conjugated polymers exhibit electrically driven volume changes when included in electrochemical devices via the exchange of ions and solvent. So far, this volumetric change is limited to 40% and 100% for reversible and irreversible systems, respectively, thus restricting potential applications of this technology. A conjugated polymer that reversibly expands by about 300% upon addressing, relative to its previous contracted state, while the first irreversible actuation can achieve values ranging from 1000–10 000%, depending on the voltage applied is reported. From experimental and theoretical studies, it is found that this large and reversible volumetric switching is due to reorganization of the polymer during swelling as it transforms between a solid‐state phase and a gel, while maintaining percolation for conductivity. The polymer is utilized as an electroactive cladding to reduce the void sizes of a porous carbon filter electrode by 85%. Abstract : Conjugated polymers exhibit electrically driven volume changes when electrochemically switched. Here, a thiophene‐based polymer reversibly expands by 300% upon addressing, relative to its previous contracted state, while the first irreversible actuation can achieve values ranging from 1000–10 000%, depending on the applied voltage. Molecular dynamics reveal that the polymer transforms between a solid state to gelled state.